Gauging the collection and services of public libraries in Pakistan. Issue 4 (15th March 2018) - Warraich, Nosheen Fatima; Malik, Amara; Ameen, Kanwal
Abstract : Purpose: Public library's core function is to meet the changing needs of challenging users by providing access to library collection and services. This study aims to explore the current status of public libraries' collection, services, users, staff, physical facilities and IT infrastructure in Punjab, the most populous province of Pakistan. It further investigates the problems faced by these public libraries and puts forward practical solution. Design/methodology/approach: This is a quantitative study based on questionnaire survey. A semi-structured questionnaire was designed to collect data. In total, 21 Library and Information Science graduates were employed to ensure the physical visit of all 176 public libraries in 36 districts of the province. Findings: The findings revealed that with a few exceptions, public libraries were mostly in a poor condition. Absence of professional staff, out-dated collections, dilapidated library buildings and lack of IT infrastructure were the major issues prevailing in the libraries. Furthermore, little interest of political leadership and higher authorities is observed in the development of public library system. Practical implications: This data will be helpful for policy and decision makers to plan and develop human resources, physical facilities and IT infrastructure in libraries. Findings may facilitate higher authorities for designing better services and strengthening public library system in the province. Originality/value: This is a baseline study on public libraries' status in the province. It aims to fill the gap by identifying total number of existing public libraries and exploring their current status along with the problems faced by these libraries.